Standard Interferon and Ribavirin Response in Patients with Chronic Hepatitis C - Muhammad Murtaza Bukhari , Amjad Mehmood , Mohammad Iqbal Khan; Tariq Masood (Journal of Rawalpindi Medical College, 2013)
Background: To study the response of standard interferon and ribavirin in patients with chronic hepatitis C. Methods: In this descriptive study 235 adult patients of hepatitis C infection who received 3 MIU interferon three times a week along with Ribavirin 1000-1200 mg/day,for a period of 24 weeks, were enrolled . End of Treatment Response (ETR) was assessed by testing HCV RNA by PCR. The efficacy of the treatment was evaluated by Sustained Virological Response (SVR) and those with detectable HCV RNA were labeled as relapsers. Results: Majority (76.74%) showed SVR undetectable HCV RNA. Out of them 78.89% were females. Relapse was encountered in 23.26% patients. Conclusion: Conventional Interferon in addition with Ribavirin administration is effective in majority of patients